Improved growth velocity of a patient with Noonan‐like syndrome with loose anagen hair (NS/LAH) without growth hormone deficiency by low‐dose growth hormone therapy. (19th June 2015) - Takasawa, Kei; Takishima, Shigeru; Morioka, Chikako; Nishioka, Masato; Ohashi, Hirofumi; Aoki, Yoko; Shimohira, Masayuki; Kashimada, Kenichi; Morio, Tomohiro
Abstract : Noonan‐like syndrome with loose anagen hair (NS/LAH; OMIM 607721) is caused by a heterozygous c.4A>G mutation in SHOC2 . Most cases exhibit both growth hormone deficiency (GHD) and growth hormone insensitivity (GHI) and thus require a high dose of growth hormone (GH) therapy (e.g., 35–40 µg/kg/day). We report on a genetically diagnosed NS/LAH patient manifesting severe short stature (−3.85 SDs) with low serum level of IGF1, 30 ng/ml. The peak levels of GH stimulation tests were within the normal range, and GHI was not observed in the IGF1 generation test. However, with low‐dose GH therapy (25 µg/kg/day) for two years, IGF1 level and height were remarkably improved (IGF1: 117 ng/ml, height SDs: −2.20 SDs). Further, catch‐up of motor development and improvement of the proportion of extending limbs to trunk were observed (the Developmental Quotient score increased from 68 to 98 points, and the relative sitting height ratio decreased from 0.62 to 0.57). Our results suggest that endocrinological causes for short stature are variable in NS/LAH and that GH therapy should be considered as a possible treatment for delayed development in NS/LAH. © 2015 Wiley Periodicals, Inc.